2009
DOI: 10.3200/jrlp.143.1.28-44
|View full text |Cite
|
Sign up to set email alerts
|

How Task Characteristics and Social Support Relate to Managerial Learning: Empirical Evidence From Dutch Home Care

Abstract: Researchers have revealed that managers profit most from informal and on-the-job learning. Moreover, research has shown that task characteristics and social support affect informal learning. On the basis of these insights, the authors examined the effects of task characteristics (psychological job demands, job control) and social support from the supervisor and colleagues on informal on-the-job learning among 1588 managers in the Dutch home-care sector. A regression analysis revealed that high demands, high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 40 publications
0
44
0
7
Order By: Relevance
“…There is also some evidence showing connections between social support and learning or professional development; there are correlations between social support and physicians’ work orientation [24], as well as general practitioners’ work practices [25]. There is some evidence that social support can develop working skills in patient–caregiver relationships [13], and social support can impact managerial learning [26]. Co-worker support is significant for professional efficacy [27] and self-efficacy [28].…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence showing connections between social support and learning or professional development; there are correlations between social support and physicians’ work orientation [24], as well as general practitioners’ work practices [25]. There is some evidence that social support can develop working skills in patient–caregiver relationships [13], and social support can impact managerial learning [26]. Co-worker support is significant for professional efficacy [27] and self-efficacy [28].…”
Section: Introductionmentioning
confidence: 99%
“…Social support from supervisors has long been recognized as important for both learning and transfer of training. Research has incorporated the use of leadership theories including transformational leadership and LMX to further our understanding of the role of social support in informal learning and knowledge sharing (Ouweneel et al 2009, Zhang et al 2011. Employees with high-quality LMX relationships with their supervisors engaged in more voluntary learning behaviors (Walumbwa et al 2009) and perceived greater organizational support for development (Kraimer et al 2011).…”
Section: Social Exchangementioning
confidence: 99%
“…Due to the challenges posed by the dynamic labor market, global competition and technological innovation, lifelong learning ranks high among the topics on the management as well as research agenda (Nijhof, 2005;Ouweneel, Taris, Van Zolingen, & Schreurs, 2009). Past research has revealed that contemporary careers can be viewed as a series of learning cycles across a person's life (Hall, Zhu, & Yan, 2002), and that learning must be examined in relation to the context in which it occurs, S 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 acquiring new social contacts (Carstensen, 1998).…”
mentioning
confidence: 99%